Industry Effects of Monetary Policy: Evidence from India - Saibal Ghosh (Indian Economic Review, 2009)
The study exploits 2-digit level industry data for the period 1981-2004 to ascertain the interlinkage between a monetary policy shock and industry value added. Accordingly, we first estimate a Vector Auto Regression (VAR) model to ascertain the magnitude of a monetary policy shock on industrial output. Subsequently, we try to explain the observed heterogeneity in terms of industry characteristics. The findings indicate that (a) industries exhibit differential response to a monetary tightening and (b) both interest rate and financial accelerator variables tend to be important in explaining the differential response.